Airblast atomization : the effect of linear scale on the mean drop size - El-Shanawany, M. S. M. R. (Cranfield University, 1978)
Stationary prefilming-cup airblast atomizers, in which the fuel is first spread into a thin cylindrical sheet and then exposed on both sides to high velocity air, have several important advantages over other common methods of fuel injection in their application to continuous combustion systems. This thesis reports the results of a detailed programme of research on airblast atomization directed primarily to the investigation of the effect of atomizer linear scale, or size, on the mean drop diameter of sprays and, to the provision of a comprehensive picture of the performance of thin-sheet airblast atomizers over a wide range of working conditions. Three geometrically similar atomizers giving cross-sectional areas in the ratio of 1 : 4 : 16 were used; covering the range of prefilming cup diameter, D, from 19.05mm. to 76.20 millimeters, and were capable of handling various liquids at flow rates from 0.003kg/s up to 0.225 kg/s, at fuel pressures below 33 x 10^ N/m^ (about 50 p.s.i.). . It was found that atomizer scale has an appreciable direct effect on atomization quality. The Sauter mean diameter of low liquid viscosity sprays increases with the 0.44 power of atomizer linear dimension (D), while for liquids of high viscosity this effect is slightly higher.